SPATIAL DISTRIBUTION OF Sitophilus zeamais (Coleoptera: Curculionidae) AND Oryzaephilus surinamensis (Col.: Silvanidae) IN A CORN STORAGE FACILITY - CERUTI, Fabiane Cristina; PINTO JR., Airton Rodrigues (Scientia Agraria, 2009)
The study describes the spatial distribution of the stored grain beetles Sitophilus zeamais (Coleoptera: Curculionidae) and Oryzaephilus surinamensis (Coleoptera: Silvanidae) collected in a corn storage facility, including the receiving and drying areas, during August 2001 to June 2002 in Videira, State of Santa Catarina, Brazil. The experiment was composed by 20 food-baited cage traps, randomly placed in the storage structure, in order to detect spots of insect infestations. A total of 77,176 insects were captured in the food-baited traps. The most abundant species were: O. surinamensis (92%) considered a secondary pest and S. zeamais (7%), which is a primary pest. Monthly the spatial distribution of the insects collected was determined and represented in graphs of seasonal distribution (four seasons) using Surfer® software. The distribution maps indicated infestation of S. zeamais in the distal areas of the storage cells and high infestation of O. surinamensis, in proximal areas of the storage cells and in the tunnel of the storage structure. This way, the monitoring with cage traps and the use of spatial distribution maps represent an indispensable tool for the previous detection of insect populations in storage structures, allowing the management of cleaning and other handling strategies to preserve the quality of the stored corn.